3D mesoscale modeling and fracture property study of rubberized self-compacting concrete based on uniaxial tension test. (December 2019) - Li, Xing; Chen, Xudong; Jivkov, Andrey P.; Zhang, Jinhua
Highlights: The first numerical simulation of 3D mesoscale model contained all the six phases of rubberized self-compacting concrete (RSCC) under uniaxial tension was conducted based on the full-curve uniaxial tension test. The mechanical property and crack formation process of RSCC was studied through the established 3D mesoscale model. The fracture mechanism of RSCC was studied by comparing the generation, growth, and development of internal cracks in the specimen through 3D mesoscale simulation result. The crack morphology of RSCC and ordinary concrete were compared and studied, the incorporation of rubber optimized the aggregate gradation, increased interfacial transition zone (ITZ) area and the porosity of the whole specimen. Abstract: Rubberized concrete is a new type of building material intended to ultilise waste rubber with a potential for significant economic and environmental benefits. However, its strength is lower than the strength of ordinary concrete due to the introduction of rubber material, which might affect its application in practical engineering. To improve the mechanical performance of rubberized self-compacting concrete (RSCC), it is a necessary to study the internal mechanisms of strength formation, degradation and failure. Based on the uniaxial tensile test of RSCC, this work reports on the development and validation of a mesoscale model of RSCC, which accounts for its heterogeneity. RSCC is considered to be composed of mortar, coarse aggregate, rubber particles, aggregate-mortar interface transition zone (A-M ITZ), rubber particle-mortar interface transition zone (R-M ITZ), and initial defects. The mesoscopic model is validated by comparing the simulation results with test results. The model is then used to analyse the mechanical properties, crack generation and propagation, and expansion of self-compacting concrete (SCC) and RSCC are compared and analysed. Further, the effects of different volume fractions of rubber on the mechanical properties of RSCC are studied. It is found that the mechanical properties and final fracture surface morphology of RSCC with different rubber content are significantly different, and the causes of these differences are discussed.